Pesan Moral Dalam Film “Nikah Muda-Rumah Baru” Karya Turah Pathayana (Analisis Wacana Teun Van Djik) - Fernando Rio Darmawan (LPPM Stikosa-AWS, 2022)
Film is one of the mass media that is effective in conveying a message to a wide audience. In general, films contain a certain moral message based on the theme raised. Nikah Muda – Rumah Baru is a short film directed by Turah Parthayana. This film is about marriage problems at a young age. The study is Karya Turah Parthayana